ANALISIS MODEL PEMBELAJARAN TEAM-ASSISTED INDIVIDUALIZATION (TAI) DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SD - Maratushsholihah Maratushsholihah; Deni Adi Putra; Fajar Setiawan (Universitas Negeri Surabaya, 2020)
ABTRACTThis study aimed to analyze the application of the Team Assisted Individualization (TAI) model to improve student mathematics learning outcomes and to determine the application of the Team Assisted Individualization (TAI) learning method at the elementary level. Differences in research subjects, places of research, and the abilities of students used in this article lead to differences in improving learning outcomes. The journals used are research journals from 2012 to 2018. The method chosen from each researcher is action research. At the same time, this type of research was qualitative research using meta-analysis methods. This research begins by searching for relevant journals in electronic media (internet). The data collection techniques were obtained from searching for relevant journals in electronic media (internet) to analyze the research. Based on the analysis, it could be concluded that the TAI learning model can improve student learning outcomes, with a total percentage reaching 89.62%. Furthermore, the application of the Team Assisted Individualization (TAI) learning model could be used as a reference to improve student learning outcome.Keywords: learning outcome, mathematic, Team Assisted Individualization. ABSTRAKPenelitian ini bertujuan untuk menganalisis penerapan model Team Assisted Individualization (TAI) dalam upaya meningkatkan hasil belajar matematika siswa dan mengetahui penerapan metode pembelajarn Team Assisted Individualization (TAI) di jenjang SD. Perbedaan subjek penelitian, tempat penelitian, dan kemampuan peserta didik yang digunakan dalam artikel ini, menimbulkan perbedaan peningkatan hasil belajar. Jurnal-jurnal yang digunakan adalah jurnal penelitian yang dimulai tahun 2012 hingga 2018. Metode yang dipilih dari tiap peneliti adalah PTK. Sedangkan jenis penelitian ini yaitu penelitian kualitatif dengan menggunakan metode meta-analisis. Penelitian ini diawali dengan mencari jurnal yang relevan di media elektronik (internet). Teknik pengumpulan data diperoleh dari mencari jurnal yang relevan di media elektronik (internet) dengan penelitian yang akan dianalisis. Berdasarkan analisis, dapat disimpulkan model pembelajaran TAI dapat meningkatkan hasil belajar siswa dengan total presentase mencapai 89,62%. Dan penerapan model pembelajaran Team Assisted Individualization (TAI) dapat dijadikan sebagai suatu rujukan untuk meningkatkan hasil belajar siswa.Keywords: hasil belajar, matematika, Team Assisted Individualization.